Analisis Public Service Motivation (PSM) pada Kebijakan Pelayanan Terpadu Satu Pintu (PTSP) Pengadilan Negeri Sengkang - Herdi Syam; Syamsiar; Asmanurhidayani; Yuniarni (Universitas Serang Raya, 2023)
Government agencies continue to simplify the flow of services, one of which is the Sengkang District Court (Sengkang District Court) through the One-Stop Integrated Service (PTSP) policy. The question arises whether this policy is in line with the Public Service Motivation (PSM) owned by employees. This article is the result of qualitative research, research data comes from observations at PTSP PN Sengkang, interviews with leaders, employees, and community service users, documentation comes from regulations related to PTSP, then analyzed using reduction, display and verification techniques which are presented narratively, the results of the study show the implementation of PTSP fulfills the elements of Public Service Motivation (PSM), namely Altruism (attitude that attaches importance to the interests of others). Norm-based (serving the public interest based on norms). Affective (commitment to public programs).